2011
DOI: 10.1007/s00299-011-1182-z
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ACA7, encoding a putative auto-regulated Ca2+-ATPase, is required for normal pollen development

Abstract: Microgametogenesis is a complex process that involves numerous well-coordinated cell activities, ending with the production of pollen grains. Pollen development has been studied at the cytological level in Arabidopsis and other plant species, where its temporal time course has been defined. However, the molecular mechanism underlying this process is still unclear, since a relative small number of genes and/or processes have been identified as essential for pollen development. We have designed a methodology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…These constructs were stably transformed into A. thaliana and GUS expression was analyzed by X-GlcA assay. The two constructs with the longest ACA7 promoters (1504 bp and 1361 bp) gave rise to GUS activity in pollen ( Figure 1B), which is in agreement with previous studies (Lucca and Leó n, 2012) and microarray data (Supplemental Figure 1). Additionally, GUS was expressed in the tips of leaves, possibly hydathodes, which was not observed for endogenous ACA7, as revealed by reverse transcription PCR ( Figure 1B and 1C).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…These constructs were stably transformed into A. thaliana and GUS expression was analyzed by X-GlcA assay. The two constructs with the longest ACA7 promoters (1504 bp and 1361 bp) gave rise to GUS activity in pollen ( Figure 1B), which is in agreement with previous studies (Lucca and Leó n, 2012) and microarray data (Supplemental Figure 1). Additionally, GUS was expressed in the tips of leaves, possibly hydathodes, which was not observed for endogenous ACA7, as revealed by reverse transcription PCR ( Figure 1B and 1C).…”
supporting
confidence: 91%
“…However, mutational studies of the pollen-specific DUO POLLEN1 (DUO1) gene, which has a conserved GRSF binding motif in its promoter, found that DUO1 expression is not regulated by this sequence; this implies that there must be other mechanisms for sporophytic repression of pollen-specific genes (Brownfield et al, 2009). Expression of ACA7, which encodes for a plasma membrane Ca 2+ P-type ATPase in A. thaliana, is restricted to pollen and its protein product is essential for proper pollen development (Lucca and Leó n, 2012). To identify cis-regulatory elements involved in regulating the pollen-specific expression of ACA7, we created six constructs with ACA7 promoter sequences of different lengths fused to the beta-glucuronidase (GUS) gene ( Figure 1A, Supplemental Table 3 for primer sequences).…”
mentioning
confidence: 99%
“…In Brassica , ACA13 was induced after both compatible pollination and compatible pollen coat treatment (Iwano et al ., ), suggesting that stigmatic ACA13 functions in the export of Ca 2+ to the compatible pollen tube, promoting successful fertilization. Another P 2B ‐type isoform, ACA7, is expressed exclusively in developing pollen grains and is required for normal pollen development (Lucca & Leon, ). Indeed, significant negative correlations between Ca 2+ ‐ATPase activity and pollen germination exist (An et al ., ).…”
Section: Ca2+ Extrusion Systemsmentioning
confidence: 99%
“…The low number of proteins was unexpected as ABC transporters constitute a large family of proteins that act as a carrier for wide array of molecules [58]. Moreover, two proteins (Solyc02g092450 and Solyc04g016260) belong to calmodulin binding Ca 2+ -ATPases (ACA) [59] that have been discussed to be essential for pollen development in Arabidopsis [60,61]. And two proteins encoding H+ ATPase (AHA:…”
Section: The Proteins Of the Endomembrane Systemmentioning
confidence: 99%